The Real-World Burden of Moderate-to-Severe Psoriasis in Patients Under Systemic Treatment from Baltic Countries: Data from the CRYSTAL Observational Study - Maigi Eisen; Ilona Hartmane; Külli Kingo; Ingmars Mikazans; Tiina Toomson; Karin Toomela; Skaidra Valiukeviciene (Medicina)
Background and Objectives: Data on disease control, treatment, and quality of life (QoL) in patients with psoriasis from Baltic countries are lacking. In this study, we aimed to assess the disease control, treatment, and QoL of patients with psoriasis in countries from Central and Eastern Europe, and we report data for the Baltic countries. Materials and Methods: In a cross-sectional, international study (CRYSTAL), we retrospectively assessed the real-world disease severity and QoL in adult patients (18–75 years) from Estonia, Latvia, and Lithuania with moderate-to-severe psoriasis receiving continuous systemic treatment ≥ 24 weeks. Analyses included 50 patients from each country and were descriptive. Results: The median disease duration was 15.2–19.9 years across the countries. Most patients (78.0% in Estonia, 100% in Latvia, and 68.0% in Lithuania) were receiving monotherapy with biological agents, mainly TNF inhibitors. An absolute PASI score ≤ 3 was achieved by 82.0%, 70.0%, and 64.0% of patients in the overall study population and 89.7%, 70.0%, and 61.8% of patients receiving biologic monotherapy in Estonia, Latvia, and Lithuania, respectively. Across the countries, impairments in QoL as expressed by a Dermatology Life Quality Index score > 5 were reported by 14.0–34.0% of patients, while 88.0–96.0% of patients were satisfied with their treatment. Conclusions: Although most patients showed low absolute PASI scores and satisfaction with their evolution after ≥24 weeks of systemic treatment, they still reported an impact on QoL. This finding underlines that further optimization of systemic treatment strategies is needed to improve outcomes in moderate-to-severe psoriasis in Baltic countries.